The Impact of Reading Interest on the Academic Performance of Elementary School Students - Dwi Noviana Komsi (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
The purpose of this study was to determine the effect of reading interest on student learning outcomes and how much contribution (significance) reading interest has on student learning outcomes. The research method uses a correlational associative approach. This research was conducted at SDN 02 Lubuklinggau. The research sample was class VI students as many as 38 students. The results showed that the independent variable (reading interest) influenced the dependent variable (learning outcomes) by 747%. The conclusion of the research reveals that there is an influence of reading interest on student learning outcomes at SDN 02 Lubuklinggau. The contribution of the results of this study as enrichment material related to the problem of low student learning outcomes is caused by the factor of low student reading interest, the role of elementary school teachers can provide learning that is based on increasing student reading interest.